An Integrative Review of Cerebral Salt Wasting Syndrome. Issue 6 (December 2020) - Oh, HyunSoo; Seo, WhaSook
Abstract : ABSTRACT: BACKGROUND: Although cerebral salt wasting syndrome (CSWS) is widely recognized, its clinical characteristics, diagnostic criteria, and management have not been clearly defined. This study was undertaken to comprehensively review current literature and provide a more complete picture of CSWS. This review also aimed to provide information for nurses on how to differentiate cerebral salt wasting syndrome from syndrome of inappropriate antidiuretic hormone secretion. METHODS: An integrative review was performed. Searches were conducted between May and July 2018. The primary information sources were CINAHL, Google Scholar, MEDLINE, PubMed, Scopus, and Web of Science. Included articles were published from 1954 to July 2018. RESULTS: The essential features of CSWS are hyponatremia, hypovolemia, and increased urine output. Treatment regimens may be determined based on the acuity and severity of hyponatremia and hypovolemia as well as evident symptoms and signs. CONCLUSION: This review may help neuroscience nurses become knowledgeable about CSWS for the drafting of appropriate nursing care plans and also be able to differentiate CSWS from syndrome of inappropriate antidiuretic hormone secretion as early as possible for timely and proper management. Abstract : Supplemental digital content is available in the text.